Fostering communication skills in entrepreneurship education - Llorente, Ignacio; Odriozola, María D; Baraibar-Diez, Elisa (Journal of Management and Business Education, 2023)
The learning process at the university demands more and more active participation from students and a greater approximation to the reality that is the object of learning. In the case of creation of companies and entrepreneurship courses, it is common for teaching to be actively organized around the development of a business plan (project-based learning) developed in a group (cooperative learning). However, in many cases, the communication dimension of the business plan, an essential task in any process of setting up a business, is not worked or it is limited to the presentation of the project to be evaluated by lecturers. In this context, this paper presents two internationalization actions developed in entrepreneurship courses with the objective of teaching how to communicate a business project, all of them with an international scope. Furthermore, the initiative objectives include the improvement of students' communication skills and competences, increase their participation in learning and evaluation processes, and facilitate them a multicultural vision of entrepreneurship provided by lecturers from other universities. The results have shown a greater involvement of the students, not only in the task of communicating their business project, but also in the interest, attention and feedback provided to the business plans of their peers, thus increasing learning through this cooperation. In addition, the participation of international lecturers has been an incentive to students to improve their communication actions.